Behavior change wheel as a tool to promote physical activity in online intervention: a case study - Couto, Nuno; Morgado, Vitor; Pereira, Tomás; Vitorino, Anabela; Bento, Teresa; Alves, Susana; Duarte-Mendes, Pedro; Cid, Luís (Frontiers in Psychology, 2025)
Introduction: Physical activity (PA) has significant health benefits. However, one in four adults does not meet the globally recommended levels of PA. Considering that PA behavior is influenced by various factors operating at multiple levels, including personal, social, and environmental factors, a single-subject behavioral change intervention was developed to promote PA behavior through online sessions. Method: Based on a one-to-one methodology, the Behavior Change Wheel (BCW) methodologymodel was used to design an intervention that was developed for 24 weeks, including eight weeks of online sessions and 16 weeks of follow-up. Results: We observed an increase of metabolic equivalent (MET-min/week) (baseline = 2970; eight weeks = 6440; 24 weeks = 6744) and daily steps (baseline = 8372; eight weeks = 10234; 24 weeks = 12142), which provides some evidence for the efficacy of online methodologies, especially in the relation one-to-one.The intervention, designed through BCW, had a positive effect in promoting more PA behavior in adults and provided evidence that can be used in further interventions that aim to increase PA levels in the population; however, future studies must be conducted to expand the evidence in other domains.